Analisis Kontribusi Sektor Pertanian Terhadap Pembangunan Wilayah Di Provinsi Bengkulu - Mujiono Mujiono; Ririn Afriani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Research purposes This study aims to analyze the contribution of the agricultural sector to regional development in Bengkulu Province using the Location Quotient (LQ) and Dynamic Location Quotient (DLQ) methods. LQ is used to identify agricultural subsectors that serve as basic (leading) sectors, while DLQ examines the growth direction of these subsectors over time. The study uses secondary data from the Central Bureau of Statistics (BPS) for the period 2020–2024, covering the food crop, horticulture, plantation, and agricultural services subsectors. The findings indicate that most agricultural subsectors in Bengkulu Province—such as food crops, horticulture, and agricultural services—are classified as basic sectors (LQ > 1). However, their growth is not considered prospective because their DLQ values are below 1. This means that although these subsectors contribute significantly at the local level, their growth is slower compared to the national level. Meanwhile, the plantation subsector is categorized as non-basic and non-prospective, as it makes a small contribution and also shows slow growth. The researchers recommend strengthening the agricultural sector through subsector-specific approaches. For basic subsectors, interventions such as equipment modernization, technology adoption, farmer institutional strengthening, and market digitalization are needed. For non-basic subsectors such as plantations, revitalization efforts, partnerships with processing industries, and product diversification are recommended. The study emphasizes the importance of transforming the agricultural sector from relying on comparative advantages to developing competitive advantages in order to promote inclusive and sustainable regional development.